Analisis Perhitungan Full Costing Pisang Crispy “Loka” Surabaya - Wahyu Surya Kartika Dewi; Desipradani, Gita (Universitas Katolik Widya Karya Malang, 2025)
The full costing approach is used in this study to examine the production costs of Crispy Banana